Intolerance of uncertainty and negative emotions among high school art students during COVID-19 pandemic: a moderated mediation analysis - Fu, Congcong; Liu, Jin; Ye, Baojuan; Yang, Qiang (Frontiers in Public Health, 2024)
Objectives A number of high school art students experience negative emotions during their preparation for the art college entrance examination, characterized by worries and fear of uncertainty. Therefore, how individual difference factors, such as intolerance of uncertainty, affect the negative emotions of students needs to be examined. Inspired by the integrative model of uncertainty tolerance, the current study seeks to explain the association between intolerance of uncertainty and negative emotions by testing the potential mediating role of psychological capital and the moderating role of family functioning. Patients and methods A total of 919 Chinese high school art students (Mage = 18.50 years, range = 16–22) participated from November 2022 to December 2022. Convenience sampling strategies were used. The participants were asked to complete the measures of intolerance of uncertainty scale, psychological capital questionnaire, depression anxiety stress scale, and family adaptability and cohesion evaluation scale. The data were analyzed using Pearson’s r correlations and moderated mediation analysis. Results Results showed that intolerance of uncertainty was positively associated with negative emotions but negatively associated with psychological capital, which in turn, was negatively associated with negative emotions. Psychological capital mediated the indirect link of intolerance of uncertainty with negative emotions. Family functioning buffered the impact of psychological capital on negative emotions. Conclusion This study can enhance our understanding of the intolerance of uncertainty on negative emotions and provide insights on interventions for high school art students’ negative emotions for educators. The interventions targeting intolerance of uncertainty, psychological capital and family functioning may be beneficial in reducing the effect of intolerance of uncertainty on negative emotions faced by high school art students.